2017
DOI: 10.3892/ol.2017.5943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins with different abundance associated with cell migration and proliferation in leiomyoma interstitial fluid by proteomics

Abstract: Abstract. Uterine leiomyoma is the most common female reproductive tract benign tumor. Little is known about protein composition and changes in the leiomyoma interstitial fluid (IF). The present study focused on changes in protein abundance in the IF of leiomyoma. Leiomyoma IFs and adjacent myometrial IFs were obtained and analyzed by two-dimensional electrophoresis (2-DE) coupled with mass spectrometry and western blotting for 2-DE data validation. A total of 25 unique proteins were observed to change signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In this study we found HSPA1A and HSPB1 to be downregulated in the leiomyoma if compared to the myometrium. In our previous study (8) we identified HSPA1A as less abundant in the leiomyoma interstitial fluid, this being in line with our present data. HSPB1 belongs to the group of small Hsps with anti-apoptotic and tumorigenic properties, and considered as important therapeutic targets, particularly in cancer pathology (25,26).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study we found HSPA1A and HSPB1 to be downregulated in the leiomyoma if compared to the myometrium. In our previous study (8) we identified HSPA1A as less abundant in the leiomyoma interstitial fluid, this being in line with our present data. HSPB1 belongs to the group of small Hsps with anti-apoptotic and tumorigenic properties, and considered as important therapeutic targets, particularly in cancer pathology (25,26).…”
Section: Discussionsupporting
confidence: 93%
“…The expression of PDIA3, HSPA5, CALR, was confirmed to be upregulated, while the expression of HSPA1A and HSPB1 was confirmed to be downregulated. The abundance of VLC was confirmed to be upregulated in the leiomyoma interstitial fluid (8).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The presence of intracellular proteins is not a problem for biomarker identification, but may be a challenge for the identification of proteins actually present in the TIF. In gynecology, this method was used in ovarian cancer [71,72,73] and leiomyoma [74,75] for the exploration of the TIF by proteomics.…”
Section: Methods For Obtaining Tif From Fresh Tissue Specimensmentioning
confidence: 99%